1992
DOI: 10.1172/jci116140
|View full text |Cite
|
Sign up to set email alerts
|

Germline variable region gene segment derivation of human monoclonal anti-Rh(D) antibodies. Evidence for affinity maturation by somatic hypermutation and repertoire shift.

Abstract: To date, there has been no systematic study of the process of affinity maturation of human antibodies. We therefore sequenced the variable region genes (V genes) of 14 human monoclonal antibodies specific for the erythrocyte Rh(D) alloantigen and determined the germline gene segments of origin and extent of somatic hypermutation. These data were correlated with determinations of antibody affinity. The four IgM antibodies (low affinity) appear to be derived from two germline heavy chain variable region gene seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 74 publications
1
67
0
Order By: Relevance
“…2). Taken into consideration of our previous findings that hemocyanin C-terminal fragment displayed homology with Ig variable regions, it would be interesting to know if these SNPs in HcSC region were derived from random somatic mutations, a process which is used during affinity maturation of Ig [25]. In support of this hypothesis, Zhang et al reported that somatic hypermutation was one of the mechanisms present in FREPs of snails to obtain molecular diversity [21].…”
Section: Discussionmentioning
confidence: 88%
“…2). Taken into consideration of our previous findings that hemocyanin C-terminal fragment displayed homology with Ig variable regions, it would be interesting to know if these SNPs in HcSC region were derived from random somatic mutations, a process which is used during affinity maturation of Ig [25]. In support of this hypothesis, Zhang et al reported that somatic hypermutation was one of the mechanisms present in FREPs of snails to obtain molecular diversity [21].…”
Section: Discussionmentioning
confidence: 88%
“…Four of the identified antibodies were RhD-specific agglutinating IgM antibodies used in blood typing, and indeed the IgM response to foreign RhD is dominated by IGHV4-34*01 antibodies (16,20). Three of the anti-RhD IgM antibodies retain the AVY sequence and are known to retain self-reactivity measured by agglutination of I/i antigen-bearing erythrocytes (20).…”
Section: Resultsmentioning
confidence: 98%
“…To extend earlier evidence that IGHV4-34+ IgD+ IgM low anergic B cells are recruited into physiological germinal center (GC) responses against foreign antigens (15), we performed a Blastn search of the National Center for Biotechnology Information (NCBI) nonredundant nucleotide database using the IGHV4-34*01 sequence. The search revealed 14 human antibodies with a hypermutated IGHV4-34*01 sequence that had been elicited in normal individuals by repeated immunization either with allogeneic RhD+ erythrocytes (16), rotavirus (17), vaccinia virus (18), or tetanus toxoid (19) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of HLA-specific B cell lines permits the analysis of their Ig H and L chain genes in terms of V family usage. Such analyses have been reported for specific B cells in other antigenic systems (9), but for alloimmunity these studies have been done on established hybridomas (21,22). The anti-HLA-A2 repertoire has been studied by phage display (23); however, this technology is unable to distinguish correct pairing of H and L chain genes within single B cells.…”
Section: Discussionmentioning
confidence: 99%